How effective are MPAs in conserving crab stocks? A comparison of fisheries and conservation objectives in three coastal MPAs in Thailand. (15th November 2017) - Jones, Estelle Victoria; Macintosh, Donald; Stead, Selina; Gray, Tim
Abstract: Mangrove forest ecosystems support aquatic species important to tropical fishing communities, but habitat degradation and over-fishing have caused coastal fishery stocks to decline. Marine Protected Areas (MPAs) are widely promoted as a management option to reverse this situation. Using swimming crabs as indicator species, this paper explores the ecological effectiveness of two community-led MPAs and one co-managed MPA in Ranong and Phang-nga Provinces in southern Thailand. Comparisons were made of two fisheries objectives: catch per unit effort (CPUE); and size frequency distribution of Portunus spp. and Scylla olivacea ; and one conservation objective: catch composition on benthic aquatic species, between each managed area and an associated control site to look for effects of management. Eight replicates of each survey were undertaken in each site: four in the wet season, from May to July 2011; and four in the dry season, from February to March 2012. Two of the MPAs, one a no-take zone and one a gear limitation zone, and both managed by local communities, showed a significant increase in CPUE of target species compared with their controls to the benefit of local fishers. There was little evidence of management impact on the composition of benthic aquatic species so community management is not achieving wider conservation in terms of increased biodiversity. The third MPA, a seasonal no-take zone, co-managed by local communities and local government, showed no significant effect on either CPUE of target species, or composition of benthic aquatic species when compared to its control. For size frequency distribution, a higher abundance of all size classes of Portunus pelagicus was observed in all MPAs compared to their control sites. The size distribution of animals suggests that the community-managed MPAs are supporting recruits and contributing to the fisheries by reducing the rates of growth overfishing. To conclude, the two community-led MPAs benefitted fishers but had no effect on marine biodiversity, while the co-managed MPA did not benefit fishers or marine biodiversity. However, all three MPAs showed increase crab abundance in each size class. Highlights: Explores the ecological effectiveness of two community-led MPAs and one co-managed MPA in Thailand. Comparisons were made on CPUE, catch composition, and size frequency distribution of Portunus spp. and S. olivacea . Two MPAs, managed by local communities, showed a significant increase in the target species compared with their controls. Seasonal no-take zone, co-managed by local communities/government, showed no significant effect on target species CPUE. A higher abundance of all size classes of P. pelagicus was observed in all MPAs compared to their control sites.